Usefulness of Palliative Prognostic Index, Objective Prognostic Score, and Neutrophil–Lymphocyte Ratio/Albumin Ratio As Prognostic Indicators for Patients Without Cancer Receiving Home-Visit Palliative Care: A Pilot Study at a Community General Hospital - Taiki Hori; Ken-ichi Aihara; Koki Ishida; Kaori Inaba; Keisuke Inaba; Yousuke Kaneko; Keisuke Kawahito; Shoki Bekku; Minae Hosoki; Kensuke Mori; Kanako Itami; Masayo Katsuse; et al. (Palliative Medicine Reports)
Background: Although the palliative prognostic index (PPI), objective prognostic score (OPS), and neutrophil–lymphocyte ratio/albumin ratio (NLR/Alb) are well-known prognostic indicators for cancer patients, they do not provide clarity when it comes to predicting prognosis in patients without cancer who receive home-visit palliative care. Objective: The aim of this study was to determine whether PPI, OPS, and NLR/Alb can predict prognosis for patients without cancer who received home-visit palliative care. Design: This is a retrospective study. Setting/Subjects: We recruited 58 patients without cancer who received home-visit palliative care from Tokushima Prefectural Kaifu Hospital, Japan, and died at home or at the hospital within seven days of admission between January 2009 and March 2023. Measurements: The PPI, OPS, and NLR/Alb of the study patients were evaluated at regular intervals, and statistical analysis was performed on the relationship between these indices and the time to death. Results: Simple regression analysis showed that PPI, OPS, and NLR/Alb were negatively correlated with the period until death (p < 0.001). The survival curves of the groups classified according to PPI, OPS, and NLR/Alb were significantly stratified. The predictive capacities of PPI, OPS, and NLR/Alb for death within 21 days were as follows: PPI (area under the curve [AUC]: 0.71; sensitivity: 59%; specificity: 68%), OPS (AUC: 0.73; sensitivity: 88%; specificity: 47%), and NLR/Alb (AUC: 0.72; sensitivity: 72%; specificity: 73%). Conclusions: PPI, OPS, and NLR/Alb were useful in predicting the survival period and short-term prognosis within 21 days for patients without cancer who received home-visit palliative care.